Decline of Indian Civilization in Habib Tanveer's Play "Agra Bazaar" - Bibi, Shamaila; Tayib, Tahir Abbas (sourcecoder, 2024)
Drama is an ancient and popular genre of literature, it has immense popularity in almost all languages of the world. Genre drama gained its popularity due to the explanations given by Aristotle and Bharata Mini. All the classical dramatists used the same principles of drama in their plays. In the West itself, writers from ancient times followed the principles presented by Aristotle. But in the second decade of the nineteenth century, the famous German dramatist Bertolt Brecht, deviating from the principles created by Aristotle, presented a new principle of dramas, "Epic Theatre" in plays. It became very popular and a new revolution was born in the world of drama and experiments were started in writing plays using this technique of Brecht in different languages. Plays were also written in Urdu inspired by this technique of Brecht. The early effects of which we find in the plays of progressive writers. But the most important and popular name among those who introduced Brecht's technique to the Urdu class in the true sense is that of Habib Tanveer. His drama "Agra Bazaar" is the first Urdu drama to introduce the epic theater technique. Through this play, Habib Tanveer has started regular dramatization in Urdu. Agra Bazaar is the milestone in the history of modern Indian theater or Urdu drama from where Urdu drama begins its journey to a new era of modernity. This drama is considered to be the link between classical and modern drama as it uses classical drama as well as modern drama techniques. The impression left in a stage presentation fade with the passage of time, but that is not the case with Agra Bazaar. Because along with changing times, Habib Tanveer has made many changes in its plot and stories to make it more interesting and meaningful.